The role of risk management on HR team effectiveness: The moderating effect of leadership style - Lasmi, Ni Wayan; Jelantik, I Gusti Ayu Agung Istri Dinda Larasshanti; Putra P, Komang Widhya Sedana (Priviet Social Sciences Journal, 2025)
The fast-changing business landscape poses challenges for Human Resource (HR) teams in Small and Medium Enterprises (SMEs) in terms of risk and performance and maintaining stability in uncertain times. Continuity and team performance depend on effective risk management. Managing risks in the literature has involved HR teams with performance and operational continuity in the business with little or no citations on the HR leadership style, which has been the primary focus of this study. This gap in understanding limits the extent to which businesses can help HR teams improve their operational performance. This study attempts to fill this gap by measuring the effect of risk management on the effectiveness of HR teams and how leadership affects this relationship. For this purpose, a quantitative survey research based on PLS-SEM was conducted on 200 HR employees and Balinese frontline operational workers in SMEs in teams oriented toward the collection of PLS-SEM data in specified domains of operational risk management. The data was collected by means of a survey employing standardized questionnaires and analyzed through focused area PLS-SEM and customized bootstrapping techniques for testing moderation through interaction terms. The results showed that the effectiveness of HR teams can be significantly enhanced through the adoption of appropriate risk management strategies. Furthermore, leadership styles that are more active in a hierarchy not only directly increase team performance but also strengthen the impact of risk management. This integration of perspectives demonstrates the practical applicability of the Resource-Based View alongside Contingency Theory: the context of leadership and organizational resources shapes team output. Looking ahead, the extension of this research could focus on longitudinal designs, additional organizational culture, and employee motivation variables for moderation or mediation, and research on a context larger than SMEs to test the breadth of this conclusion.